The Spread and Importance of Iatric Cults in the Antiquity with Special Reference to the Cult of Asclepius and His Veneration in Naissus - Ljubomirovic, Irena; Radulovic, Nenad (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
Iatric cults were spread in Hellas, and in the Hellenistic period were also venereted in Roman Empire. The most famous were Asclepius and his daughter Hygeia. Asclepius was famous Greek physician whose divine nature helped to heal the patients, which is why he was very popular among people. That’s why he was popular among people. Asclepius was the only Greek deity to be accepted in the Temple of Westphalia in Rome, which means that the Romans thoroughly accepted him as very important deity in the Roman religion. He was considered to be the guardian of the individuals as well as the whole families, in addition, the protector of soldiers and even emperors. Sanctuaries were built in his honor, but he was also revered in sanctuaries of other gods. The healing power of Asclepius was associated with hot and cold water springs for use of water in the healing process which was very respected since the water was used in healing processes. It is assumed that one shrine was placed in imperial villa in Mediana, due to near hot water source in Niška banja. The veneration of cult of Asclepius in Mediana is traced back to the Roman emperor Julian and his restoration to paganism. Although Julian ruled for a short period of time, the statues of Asclepius and Hygeia remained in the villa in Mediana for decoration, only to be destroyed during the Hun devastation of Nais in 378.The need to prevent and cure people form deadly infectious diseases, which took many lives, had caused the respect of the cult of Asclepius in the territory of Hellas, Asia Minor and most part of Roman Empire in the period from the 16th century BC until the 6th century AD. From ancient time, people felt the need to take care of their own health, and when there was no other way to be cured, Asclepius helped with his supernatural power. His ability and readiness to provide help to everyone who needed it, made him the most widespread and respected cult of healing.
Keywords: Asclepius; Hygieia; healing; water source; Mediana